2016
DOI: 10.1038/npp.2016.150
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Seeking During Initial Abstinence Is Driven by Noradrenergic and Serotonergic Signaling in Hippocampus in a Sex-Dependent Manner

Abstract: There is evidence for sex differences in cocaine addiction from both clinical and preclinical studies. In particular, preclinical studies indicate that females may be more sensitive than males to stress-induced drug seeking. The dorsal hippocampus (DH) is prominently involved in the stress response, as are the locus coeruleus norepinephrine (LC-NE) and dorsal raphe serotonin (DR 5-HT) systems. Moreover, DH receives strong inputs from LC-NE and DR 5-HT neurons. We hypothesized that the stress associated with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 63 publications
6
31
0
Order By: Relevance
“…Moreover, the current findings are also in line with several neural cue‐reactivity studies in nicotine dependence (Cosgrove et al., ; Dumais et al., ). Animal studies have also reported that acute and chronic alcohol exposure only alters striatal mRNA expression in male, but not in female rats (Baxter‐Potter et al., ) and that there is a differential involvement of serotonergic and noradrenergic signalling in cue‐induced reinstatement (Kohtz & Aston‐Jones, ). Altogether, the current study supports the hypothesis that different (neural) mechanisms may underlie the development and persistence of substance use disorders in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the current findings are also in line with several neural cue‐reactivity studies in nicotine dependence (Cosgrove et al., ; Dumais et al., ). Animal studies have also reported that acute and chronic alcohol exposure only alters striatal mRNA expression in male, but not in female rats (Baxter‐Potter et al., ) and that there is a differential involvement of serotonergic and noradrenergic signalling in cue‐induced reinstatement (Kohtz & Aston‐Jones, ). Altogether, the current study supports the hypothesis that different (neural) mechanisms may underlie the development and persistence of substance use disorders in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…A candidate gene association study found an association with variants of HTR1A with suicide attempts in alcohol dependent patients (Wrzosek et al, 2011). A 5HT1A/B antagonist (WAY100635) reduces drug seeking during initial abstinence in rats (Kohtz and Aston-Jones, 2017). In addition, serotonin specific neuronal reduction in expression of Htr1A in mice contributes to cocaine seeking behavior and inhibition of dorsal raphe 5-HT1A autoreceptors attenuates cocaine self-administration in rats with prolonged extended access, but not 1 h access to the drug (You et al, 2016).…”
Section: Genome-wide Association Studies Of Alcohol Dependencementioning
confidence: 99%
“…For example, females show greater CRF receptor binding affinity; increased serotonin synthesis; and increased adrenergic, corticosterone, and GABA receptor expression compared with males (Turner, 1992;Madeira and Paula-Barbosa, 1993;Galea et al, 1997;Rhodes and Rubin, 1999;Shors et al, 2001). In addition, findings from a recent study by Kohtz and Aston-Jones (2016) demonstrate that selective inhibition of b-ARs with S-propranolol or with a cocktail of selective b-AR antagonists betaxolol 1 ICI-118,551 microinjected into the DH attenuates drug seeking during initial abstinence (ED1; F 1,40 5 5.083, P < 0.05). Post hoc analyses reveal that the betaxolol 1 ICI-118,551 cocktail was Fig.…”
Section: Lc-ne and Downstream Neuralmentioning
confidence: 93%
“…It is unclear whether increased responding on ED1 in females is dependent on estrous cycle of the female rat (Feltenstein and See, 2007;Feltenstein et al, 2009). In a recent article, the authors hypothesized that the initiation of abstinence, ED1, is stressful because of the absence of drug, thereby engaging the CRF and NE systems to promote increased cocaine seeking (Cason et al, 2016;Kohtz and Aston-Jones, 2016). This hypothesis was tested by blocking CRF1 signaling using a selective CRF1 receptor antagonist, 526 (CP), and investigating the impact on drug seeking on ED1 measured by responding on an active lever previously associated with cocaine self-administration.…”
Section: Crf and Norepinephrine In Stress-induced Withdrawal Andmentioning
confidence: 99%